2008
DOI: 10.1007/s11524-008-9333-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Identifying as a Barebacker among High-Risk New England HIV Seronegative Men Who Have Sex with Men

Abstract: Studies have found that between 14% and 46% of US men who have sex with men (MSM) consistently report "barebacking" behavior (i.e., intentional unprotected anal intercourse) with other men. This is of public health significance because MSM continue to constitute more than 50% of new HIV infections in the USA. Men who self-identify as barebackers may represent a different and unique subset of MSM with distinct HIV prevention needs. In 2007, 227 HIV seronegative MSM recruited through modified respondent-driven s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 42 publications
1
22
1
3
Order By: Relevance
“…Barebacking A series of five questions used in previous MSM research assessed participant knowledge and understanding of barebacking [17]. Participants were asked whether or not they self-identified as a barebacker, and they were asked to consider whether or not four scenarios constituted barebacking, including ''having anal sex with someone and deliberately not using condoms although you are not sure you are both HIV-negative'' and ''having anal sex with condoms but the condom breaks''.…”
Section: Characteristics Of Sex Parties and Hiv And Std Risk Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Barebacking A series of five questions used in previous MSM research assessed participant knowledge and understanding of barebacking [17]. Participants were asked whether or not they self-identified as a barebacker, and they were asked to consider whether or not four scenarios constituted barebacking, including ''having anal sex with someone and deliberately not using condoms although you are not sure you are both HIV-negative'' and ''having anal sex with condoms but the condom breaks''.…”
Section: Characteristics Of Sex Parties and Hiv And Std Risk Inmentioning
confidence: 99%
“…Private sex parties may be an especially important type of GSE regarding HIV sexual risk among MSM [2,6,7,15]. Between 8 and 25% of MSM in various studies report having met recent male sex partners at private sex parties [6,16,17], and meeting sexual partners at sex parties has been associated with high-risk sexual behavior [6,7,9]. Bareback sex parties have been associated with particularly high-risk behaviors among MSM.…”
Section: Introductionmentioning
confidence: 99%
“…3,17 These event-level assessments of alcohol use provide the most precise temporal link between these two behaviors and provide stronger evidence for causality. 2,17 Binge drinking and other patterns of heavy alcohol use are independently associated with a variety of high-risk behaviors in MSM, including unprotected anal sex, multiple partners, and having HIV-serodiscordant partners, [18][19][20][21][22][23][24][25][26][27][28] a link also observed among Black, Native American, and older MSM. [29][30][31] Binge drinking and heavy alcohol consumption are major causes of incident HIV infections in MSM.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have identified sexual behavior factors, such as engaging in a variety of unprotected sex acts and having casual partners (Berg, 2008;Elford et al, 2007;Halkitis et al, 2005;Mansergh et al, 2002;Reisner et al, 2008), as being related to barebacking. Further, health behavior factors like recreational drug use have been found to be associated with bareback sex (Berg, 2008;Elford et al, 2007;Kelly, Bimbi, Izienick, & Parsons, 2009;Reisner et al, 2008;Wilton, Halkitis, English, & Roberson, 2005). Other research has suggested that perceptions about HIV, notably cognitions about improved HIV drug treatments, has lessened MSM's worry about HIV and contributed to their decision to bareback (Elford et al, 2007;Mansergh et al, 2002).…”
Section: Introductionmentioning
confidence: 99%